Kurangnya Komunikasi Interpersonal Orang Tua pada Anak Memicu Terjadinya Kenakalan Remaja di Desa Pisang Pala Kecamatan Galang - Saydina Maya Tanjung; Susilawati Siregar; Jirza Raisa Fahira; Arif Zidansyah; Diky Syahputra (Al-Balagh : Jurnal Komunikasi Islam, 2022)
Aspects of communication are very important in the process of child growth, one of which is interpersonal communication which is a two-way communication to improve relationships between individuals, especially parents and children. But in the midst of the rampant negative influences that occur in the outside world, it requires parents to be more involved in the growth and development of children and one of them when communicating. Because poor communication between children and parents can have a negative impact on children's emotional development, so children are more individualistic. As in Pisang Pala Village, Galang District, this village is indeed a supporting factor for the occurrence of juvenile delinquency due to the lack of interpersonal communication between parents and children. So in this paper, it aims to describe the condition of adolescents' attitudes towards their parents and how to overcome them, using qualitative research methods. Therefore, communicating with each other is very important for parents to children, so that children can express their feelings so that they have a healthy personality